Faktor-faktor yang Berkaitan dengan Kejadian Keracunan Pestisida Pada Tenaga Kerja Teknis Pestisida Perusahaan Pemberantasan Hama (Pest Control) di Kota Semarang Tahun 2002 - Praptini, Titiek; Sulistiyani, Sulistiyani; Suhartono, Suhartono (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2003)
ABSTRACK Background : Pesticide plays an important role in controlling disease vector in the area of pest control. The use of pesticide is increasing and so does the number of pest controlcompanies, which is accompanied by an increase in the number of pesticide technical workers. Based on the data of Health Service of Province of Central Java, it is found that 25% of workers are poisoned with pesticide. The aim of this research is to know the factors related to the event of pesticide poisoning in Pesticide Technical Workers of Pest Control Company in Semarang City in the Year 2002. Methods : The type of this research was confirmatory research. The sample of this research was total population of pesticide technical workers of pest control companies in Semarang City amounted to 86 persons. Variables analyzed were age, tenure, anemia status, nutrient status, knowledge, attitude, and practices of respondents. The data collected by interview, observation, and the measurement of Hb level, nutrient status collected by IMT and cholinesterase activity examination. The data analyzed by using Chi Square with Âµ = 0.05. Result : Research show that there are 38 (44.2%) pesticide technical workers who have already been poisoned with pesticide. The result of statistical analysis with Chi Square show that there is a correlation between anemia status and practice of spraying and the event of pesticide poisoning with p < 0.05. It is hoped that the employers and pesticide technical workers obey the rules and requirements of health on the use of pesticide. Keyword : Pesticide, Poisoning, Workers, Pest Control